Reimbursement Application Using Rest API Methods and Android-Based Flutter Framework (Case Study: PT. Protonema) - Renardi, Febby; Faizah, NM; Koryanto, Lucky (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
PT. Protonema is a company engaged in the field of information technology, namely as a consulting partner in Jakarta. This company has provided various kinds of facilities to employees to support their work and simultaneously to improve their quality of life who are concerned about the importance of self-development and provide health insurance. Employees can submit claims to obtain these facilities by attaching receipts as further evidence that the company reimburses the costs that have been incurred, this is often referred to as reimbursement. Submission of reimbursement by employees based on the current process has problems, such as the absence of notification of claims submitted by employees whether the claim is accepted or rejected and still using Microsoft Word which is eventually printed into this archive, it is feared that it will be lost or forgot to save it because scattered archives. The purpose of writing this research is to produce an Android-based reimbursement submission application at PT. Protonema with the REST (Representational state transfer) API (Application Programming Interface) method as a data exchange medium and supported by MySQL so that data processing is precise and safe because it is stored in a database and other supports, namely the Flutter framework, are used to design Android applications. In making this software using the waterfall model and data collection techniques, namely observation, interviews and literature study. From this research, it can be concluded that an Android-based reimbursement application using the REST API method and supported by MySQL can help PT. Protonema in managing employee reimbursement applications more efficiently and effectively. By using this application, employees can submit reimbursement requests easily and quickly via their cellphones, and the data obtained will be recorded correctly and safely in the database. The use of the Flutter framework also helps in designing the appearance and functionality of applications that are easier to use and accessible to employees. Therefore, this application can be an effective solution to increase the efficiency and effectiveness of employee reimbursement management at PT. Protonema.